Best practices of designing user interfaces for children - Niemi, Kimmo (My University, 2020)
When developing software interfaces for children, there are some considerations to be made to the software development, since children think and act different from adults and compared to adults, children have physical and cognitive limitations that present challenges to using computer technology. Identifying existing guidelines and best practices for designing software interfaces for children that enables developers to take into account the limitations of children was the main research topic of this thesis. Identified existing guidelines were summarized, and based on that summarization it was concluded, among other things, that the interface should be designed in a way that the younger the children are, the more simplified and easier to use the design should be. Besides summarizing the guidelines, this thesis also examined prominent theories of cognitive development in the context of computer interfaces, and also examined a web-based research tool called Neurone. A new use case for Neurone was developed as a part of a University of Turku research project, and the use case was analyzed by the summarized guidelines for designing software interfaces for children. Neurone research tool with the newly developed use case was used by a group of 12-year-old children. The group was asked to answer a questionnaire in order to collect feedback for the usability of the Neurone interface including the use case. Results of the questionnaire are analyzed and presented in the thesis.
Keywords: interfaces, interface design for children, cognitive development